Beyond precision: Spirituality, ethics, and emotional experience among venezuelan medical Physicists (Research, Society and Development, 2025)
Background: Medical physicists work in highly sensitive clinical environments, particularly in radiotherapy services, where the primary focus is on oncology patients. In these settings, contact with human suffering, death, and expressions of faith is a daily occurrence. Objective: The aim of this study was to conduct an initial exploration of how medical physics professionals trained at Venezuelan universities navigate the intersection of their technical-scientific education, clinical training, and personal beliefs. The study also examines their strategies for coping with these new situations and their perceptions of institutional and spiritual support. Method: The analysis was carried out through thematic coding and phenomenological interpretation. Results: Most respondents identified themselves as participants in or closely connected to religious or spiritual practices. However, their experiences tend to be oriented more toward introspection, ethics, and personal reflection than toward formal rituals. Conclusion: Medical physicists, whose foundational training in physics is rooted in scientific faculties, engage with profoundly human dimensions of care in oncology patients. Spirituality, broadly understood, emerges as a significant tool for emotional balance, resilience, and ethical grounding in clinical practice.